Studying C-reactive protein and D-dimer levels in blood may prevent severe complications: A study in Bangladeshi COVID-19 patients - Sultana, Gazi Nurun Nahar; Srivastava, Anshika; Akhtaar, Khalida; Singh, Prajjval Pratap; Islam, Md. Anarul; Mishra, Rahul Kumar; Chaubey, Gyaneshwer (Frontiers in Genetics, 2022)
The ongoing COVID-19 pandemic has been a scientific, medical and social challenge. Since clinical course of this disease is largely unpredictable and can develop rapidly causing severe complications, it is important to identify laboratory biomarkers that may help to classify a patient’s severity during the initial stage. Previous studies have suggested C - reactive protein (inflammatory) and D-dimer (biochemical) as an effective biomarker. The differential severity in patients worldwide and our limited understanding of the progression of the disease call for a multi-country analysis for biomarkers. Therefore, we have analyzed these biomarkers among 228 Bangladeshi COVID-19 patients. We show a significant association of COVID-19 severity with these two biomarkers. Thus, we suggest using these biomarkers for Bangladeshi COVID-19 patients for disease monitoring. Such validated preventive measures may decrease the case fatality ratio substantially.